Effects of Ownership on Hospital Efficiency in Germany - Oliver Tiemann; Jonas Schreyögg (BuR - Business Research, 2009)
The objective of our study was to evaluate the efficiency of public, private for-profit, and private non-profit hospitals in Germany. First, bootstrapped data envelopment analysis (DEA) was used to evaluate the efficiency of a panel (n = 1,046) of public, private for-profit, and private non-profit hospitals between 2002 and 2006. This was followed by a second-step truncated linear regression model with bootstrapped DEA efficiency scores as dependent variable. The results show that public hospitals performed significantly better than their private for-profit and non-profit counterparts. In addition, we found a significant positive association between hospital size and efficiency, and that competitive pressure had a significant negative impact on hospital efficiency.
urn:nbn:de:0009-20-21700
Keywords: 650; Germany; data envelopment analysis; non-parametric technique; ownership; performance measurement; public hospitals; truncated regression; Krankenhaus; Eigentum; Wirtschaftliche Effizienz; Data-Envelopment-Analyse; Schätzung; Deutschland